PENGARUH KOMUNIKASI PEMASARAN TERPADU TERHADAP PROSES KEPUTUSAN PEMBELIAN PRODUK TOLAK ANGIN - Reiza Benyamin; Martani Huseini (LPSDI Bina Patria, 2024)
Business competition occurs in this era of globalization between the conventional market communications industry and the integrated market communications sector. Therefore, in choosing a product, customers can choose a product that meets their needs and desires. The purpose of this research is to try to find out how much influence integrated marketing communications has on the current decision process for purchasing Tolak Angin products. In this research, a quantitative approach with an explanatory nature is used, with a research target of 100 respondents who are graduate students at Pelita Harapan University Class of 2018, faculty of communication, with fill out a questionnaire in the form of a Google Form. The questions asked to respondents are considered valid and reliable. The R-square value in this study was 3.4%. The F test has a value of 3.423 which is greater than F table so it has an influence. Meanwhile, to test the hypothesis itself, it has a value of 1.850 which is greater than the T table value so that Ha is proven. This research produces an indication of a positive value or hypothesis of the influence between the Integrated Marketing Communication variable (X) and the Purchase Decision Process variable (Y) which is proven, even though the value that influences These two variables are small, only 3.4%, so this research can answer the problem formulation and objectives that the researchers have prepared.